2022
DOI: 10.3390/healthcare10010119
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Maintenance Strategies after Pulmonary Rehabilitation: Perspectives of People with Chronic Respiratory Diseases, Informal Carers, and Healthcare Professionals

Abstract: Pulmonary rehabilitation (PR) is an effective intervention for people with chronic respiratory diseases (CRD); however, its effects fade after 6–12 months. Community-based strategies might be valuable to sustain PR benefits, but this has been little explored. People with CRD, informal carers, and healthcare professionals (HCPs) were recruited from pulmonology appointments of two local hospitals, two primary care centres, and one community institutional practice and through snowballing technique. Focus groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
(39 reference statements)
1
4
0
Order By: Relevance
“…1 , 7 , 11 , 39 Despite this, significant clinical resources are devoted to maintenance programs and some patients may find them useful to maintain motivation for physical activity, and to access support from peers and health professionals. 40 The data in this review illustrate the evolving body of evidence for an alternative approach of repeating pulmonary rehabilitation, and supports calls for access to repeat programs. 8 However, resource reallocation would require more evidence not only for clinical measures but also incorporate the impact of repeat programs on outcomes such as healthcare utilization, for which hospitalization forms the bulk of direct medical costs.…”
Section: Discussionsupporting
confidence: 53%
“…1 , 7 , 11 , 39 Despite this, significant clinical resources are devoted to maintenance programs and some patients may find them useful to maintain motivation for physical activity, and to access support from peers and health professionals. 40 The data in this review illustrate the evolving body of evidence for an alternative approach of repeating pulmonary rehabilitation, and supports calls for access to repeat programs. 8 However, resource reallocation would require more evidence not only for clinical measures but also incorporate the impact of repeat programs on outcomes such as healthcare utilization, for which hospitalization forms the bulk of direct medical costs.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, only one carer and one interested citizen participated, demonstrating the researchers' difficulty in attracting this public and integrating their vision. Challenges in recruiting these stakeholders have been previously acknowledged 43 . Despite the selection bias, this work was a necessary first step to give voice to patients and the public and start the process of cocreating a PPI network in respiratory research.…”
Section: Discussionmentioning
confidence: 96%
“…Challenges in recruiting these stakeholders have been previously acknowledged. 43 Despite the selection bias, this work was a necessary first step to give voice to patients and the public and start the process of cocreating a PPI network in respiratory research.…”
Section: Topic 1: Willingness To Participate In a Ppi Initiativementioning
confidence: 99%
“…One previous study showed that 70% of the patients have difficulty in maintaining endurance activities 3 months after PR, and this difficulty is influenced by disease-related symptoms and functional limitations in some patients, while others report barriers to exercise related to costs, family and exercise facilities [56]. Lack of self-efficacy, motivation and fear of exercise without supervision are other common reasons for patients not to engage in exercise/PA behaviours at home [57,58]. Repeating PR in regular periods can avoid the deterioration in exercise capacity, dyspnoea, and HRQoL [55].…”
Section: Most Research About the Effectiveness Of Pa Coaching Interve...mentioning
confidence: 99%
“…Nevertheless, studies diverged in the type of technology employed and its features, components of the maintenance intervention (e.g., exercise training, education, monitoring), equipment required for the exercise training component, type/timing of training provided on how to use the technology, and frequency of contact with HCPs (not reported in two studies [64,65]). Previous research has shown that professional support after PR is highly valued by patients to enhance their motivation to remain physically active [57,58]; therefore, it should be a component to consider in future studies. The initial PR programme may also play a role in the success of these interventions, as patients need to achieve sufficient gains during PR to be sustained with the maintenance programme [62].…”
Section: Most Research About the Effectiveness Of Pa Coaching Interve...mentioning
confidence: 99%